(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate antioxidant compounds in the glazing process for the conservation of tilapia fillets. For this, four treatments were tested: control (without addition of antioxidants), butyl-hydroxy-toluene (BHT), turmeric and β-carotene. The addition of antioxidants was done along with the glazing process, then the fillets were refrigerated for 10 days. Proximate composition, biochemical and lipid peroxidation analyzes were performed on the fifth day and at the end of the experiments (tenth day). The use of turmeric or β-carotene resulted in a lower amount of ammonia (1.06±0.10 and 1.42±0.07 µmol/g, respectively), indicating a lower putrefaction process, compared to the use of BHT (2.32±0.09). In the analysis of TBARS there was a decrease, around 50%, in fillets submitted to treatments with turmeric or β-carotene (1.71±0.51 and 1.87±0.32 nmol MDA/mg protein, respectively) compared to the control (without antioxidant). The results prove the importance of using antioxidants, such as turmeric and β-carotene, which acted by improving conservation (decreasing the action of reactive species and putrefaction), contributing to a better physicochemical quality of the fillet. The use of antioxidants in the glazing of fillets is recommended, such as β-carotene and turmeric, which, as they are natural, could be better options for use in fish processing when compared to synthetic products.